2023
DOI: 10.3390/ma16020569
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Biochar from Wood Gasification to Retain Endocrine Disrupting Chemicals

Abstract: In this study, a biochar obtained from poplar wood gasification at a temperature of 850 °C was used to adsorb the xenoestrogens 4-tert-octylphenol (OP) and bisphenol A (BPA) and the herbicide metribuzin from water. Scanning electron microscopy (SEM-EDX) and Fourier-transform infrared (FTIR) spectroscopy were employed to investigate the surface micromorphology and functional groups composition of biochar, respectively. The study of sorption kinetics showed that all compounds achieved the steady state in less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…The char was characterized by 74.5 and 8.8 %, carbon and ash content. The authors reported a very rapid sorption with a prominent role of hydrophobicity in the sorption process [65].…”
Section: Organic Micropollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The char was characterized by 74.5 and 8.8 %, carbon and ash content. The authors reported a very rapid sorption with a prominent role of hydrophobicity in the sorption process [65].…”
Section: Organic Micropollutantsmentioning
confidence: 99%
“…The authors report a high q m of 520 mg g −1 that was attributed to the structural modification of char resulting in a material similar to graphite and with an improved adsorption performance [59]. Carnimeo et al explored the potential of poplar wood GC for the adsorption of xenoestrogens 4-tert-octylphenol and bisphenol A and the herbicide metribuzin from water [65]. The char was characterized by 74.5 and 8.8 %, carbon and ash content.…”
Section: Organic Micropollutantsmentioning
confidence: 99%